Merdeka Belajar dalam Perspektif Teori Belajar Kognitivisme Jean Piaget - Wahyuni, Tri; Uswatun, Nurul; Fauziati, Endang (Lembaga Yasin AlSys, 2023)
The curriculum should need to be evaluated dynamically and periodically following the times, especially science and technology. The curriculum is also structured by taking into account the competencies needed by the community and graduates. The Free Learning Curriculum is one of the new policies of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia (Kemendikbud Ristek RI) which is aimed at realizing an innovative learning process and following the needs of students (student-centered). This 21st century learning model requires students to achieve 4C skills, namely critical thinking, communication, collaboration, and creativity. This is very relevant to the implementation of Jean Piaget's cognitivism learning theory which argues thatlearning will be more successful if it is adjusted to the stage of cognitive development of students. So that students should be given the opportunity to conduct experiments with physical objects, which are supported by interactions with peers and assisted by insightful questions from the teacher.In addition, Jean Piaget's perspective on cognitivism learning theory is very relevant because independent learning emphasizes process rather than results. This is proven by the application of independent learning which emphasizes the learning process by building student character. The independent learning assessment is not only limited to ranking because it emphasizes that the talents and intelligence of students have different abilities according to their respective fields. It is known that in independent learning there is no Minimum Completeness Criteria. So it is in accordance with the learning theory of cognitivism which emphasizes the process rather than learning outcomes. This research uses descriptive qualitative method. The results of this study were obtained from a review of several literatures.